Synthesis of Epoxy Monoethanolamide from Bauhinia monandra Seed Oil - Adewuyi, Adewale; Oderinde, Rotimi A. (Makara Journal of Technology, 2020)
In this study, we synthesized epoxidised monoethanolamide (EMA) from Bauhinia monandra seed oil (BMO) via a simple reaction route. In this process, BMO was transesterified to obtain a mixture of methyl esters, which was subjected to a urea adduct complexation reaction. The unsaturated methyl esters (BME) from the urea adduct complexation reaction were then epoxidised using performic acid produced in situ in a one-pot reaction system. The epoxidised methyl esters were converted to EMA by reacting them with monoethanolamine (1:10). The progression of the reaction was monitored using Fourier transform infrared spectroscopy and proton nuclear magnetic resonance spectroscopy, and the fatty acid composition was determined by gas chromatography. The results indicate that the most abundant fatty acid in BMO is C18:1 (25.70% ± 0.20%), with a degree of unsaturation of 49.00% ± 0.50%. After the urea adduct complexation reaction, the degree of unsaturation increased to 95.20% ± 0.10% with C18:2 (75.00% ± 0.10%) becoming the most dominant fatty acid. The oxirane oxygen content was found to be 5.50% ± 0.50%. The results of this study suggest that the urea adduct complexation reaction offers a potential means for increasing the unsaturation of fatty methyl esters. In addition, our findings show that EMA can be produced at low or room temperature.